Uma proposta de jogo didático para o ensino da teoria da evolução biológica - Isabela Maria Silva Leão (2023)
Considering the difficulties in teaching biological evolution, this case study aimed to create an educational game with a theme focused on the theory of Natural Selection. The inspiration for the product developed is the game Dixit, which was released in 2008 and sold millions of copies. Dixit can be an effective tool to be applied in educational institutions and has potential to develop students' creativity and interpretation, as the game involves the use of imagination. The purpose through the application of this tool was to contribute in a playful approach to the teaching and learning process about evolutionary theories, especially natural selection. In addition, the game was based on Brazilian biodiversity. In this way, in addition to expanding understanding about the origin of biological diversity, the game also expanded students' knowledge about species and typical environments of our country. The research was conducted with students from the 3rd year of high school from a state school in the city of Candeias in the state of Minas Gerais. The data of the research were collected from the observation of the game's application. After collecting the data, the sociomaterial relationships presented in the classroom during the game's application were analyzed. This analysis was based on Actor-Network Theory with the purpose of understanding the effects that the developed game contributed in the learning of the theory of natural selection. The Iramuteq program was also used in the analyses. The results indicate that some students had difficulties to recognize some game species. In addition, the Iramuteq program showed, from maximum trees, the mobilization of knowledge about natural selection, mainly related to species survival. The results indicate that the game created knowledge about the theory of natural selection. While the students played, questions about adaptation and biodiversity were addressed. We identified that some elements affected the students' actions, such as the images of species and environments on the game cards, the descriptions of the environments in the rulebook, the amount of time given for the students to play, among others. These elements were fundamental to understanding how the students' perception of biodiversity and adaptation is performed through the Dixit game.